The development of modern South Korea : state formation, capitalist development and national identity - Kim, Kyong Ju, 1966- (Routledge advances in Korean studies, 2006)
This book provides a comprehensive analysis of South Korean modernization by examining the dimensions of state formation, capitalist development and nationalism. The book highlights the most characteristic features of South Korean modernity in relation to its historical conditions, institution traditions and cultural values paying particular attention to Korean's pre modern civilization.